2020
DOI: 10.1002/alz.12065
|View full text |Cite
|
Sign up to set email alerts
|

Intensive weight loss and cognition: The dynamics of persistent organic pollutants in adipose tissue can explain the unexpected results from the Action for Health in Diabetes (Look AHEAD) study

Abstract: Objective The aim of this paper is to propose a new hypothesis for the role of lipophilic chemical mixtures stored in adipose tissue in the development of dementia. Specifically, we present how the dynamics of these chemicals can explain the unexpected findings from the Action for Health in Diabetes (Look AHEAD) study, which failed to show long‐term benefits of intentional weight loss on cognition, despite substantial improvements in many known risk factors for dementia. Moreover, we discuss how the role of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In addition to genetics and aging, environment pollutants have recently been considered as a risk factor that affects elder adults' cognition functions [6]. Toxicological studies have found that the exposure of persistent organic pollutants (POPs) can result in severe issues in the central nervous system, including the MCI [7]. As the typical POPs, polychlorinated biphenyls (PCBs) are a group of organochlorine compounds synthesized by biphenyl chlorination, with a total of 209 homologs [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genetics and aging, environment pollutants have recently been considered as a risk factor that affects elder adults' cognition functions [6]. Toxicological studies have found that the exposure of persistent organic pollutants (POPs) can result in severe issues in the central nervous system, including the MCI [7]. As the typical POPs, polychlorinated biphenyls (PCBs) are a group of organochlorine compounds synthesized by biphenyl chlorination, with a total of 209 homologs [8].…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 This unanticipated consequence can be attributed to the POP dynamics observed during intentional weight loss. 31 , 32 It is important to note that weight fluctuation, a common result of intentional weight loss, can lead to redistribution of POPs from adipose tissue to critical organs, as observed in animal experimental studies. 33 …”
mentioning
confidence: 99%
“…29,30 This unanticipated consequence can be attributed to the POP dynamics observed during intentional weight loss. 31,32 It is important to note that weight fluctuation, a common result of intentional weight loss, can lead to redistribution of POPs from adipose tissue to critical organs, as observed in animal experimental studies. 33 The role of adipose tissue in storing POPs and other environmental pollutants may not be trivial and can explain many puzzling findings on obesity observed in epidemiological studies.…”
mentioning
confidence: 99%
“…3 Importantly, PE can effectively remove persistent organic pollutants (POPs) that have recently emerged as a novel risk factor for dementia. 4,5 Human adipose tissue is contaminated by a large number of environmental pollutants, yet this is often ignored by researchers and clinicians. 6 The most problematic chemicals in terms of neurodegenerative disease risk would be POPs as many of them are well-known neurotoxins.…”
mentioning
confidence: 99%
“… 3 Importantly, PE can effectively remove persistent organic pollutants (POPs) that have recently emerged as a novel risk factor for dementia. 4 , 5 …”
mentioning
confidence: 99%